EVALUASI PENGGUNAAN DANA BOS BERDASARKAN RENCANA KEGIATAN DAN ANGGARAN SEKOLAH (RKAS) DI SMP NEGERI 6 PEKANBARU - Pawaka, Lestarie; Herlinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on evaluating the utilization of School Operational Assistance (BOS) funds at SMP Negeri 6 Pekanbaru, specifically assessing the alignment between the previously prepared School Activity and Budget Plan (RKAS) and actual expenditures. The background of this research stems from the importance of accountability and transparency in school financial management to support the improvement of education quality. The research employs a descriptive qualitative approach, involving a review of documents such as the RKAS for the last fiscal year, budget realization reports, and meeting minutes related to budget planning and evaluation. Additionally, semi-structured interviews were conducted with six key informants: the School Principal, BOS Treasurer, teachers, and school committee representatives, to gain a more in-depth and contextual understanding. Research findings reveal that, in general, BOS fund utilization has followed RKAS guidelines, particularly in supporting learning activities, digital literacy, student potential development, and school facility maintenance. Nevertheless, implementation on the ground still faces several challenges, including discrepancies between initial budget planning and actual realization, suboptimal oversight, delays in fund disbursement, and a fairly complex administrative burden. Despite these challenges, the school demonstrates a commitment to transparent and accountable fund management. Therefore, continuous improvement efforts in planning, implementation, and evaluation are crucial to ensure more effective BOS fund utilization and a positive impact on education quality.